EARN MONEY MAKER TRAINING FOR ANDROID TO INCREASE PASSIVE INCOME FOR RESIDENTS IN MANGUNSARI VILLAGE GUNUNGPATI DISTRICT, SEMARANG CITY - Paramita, Patricia Dhiana; Adhi, Daniel Kartika; Nurkholik, Nurkholik; Widyastuti, Ika Aprilia (STIE Pelita Nusantara, 2025)
Today, the rapid development of the smartphone world must be followed by the mindset of society so as not to be left behind. Sophisticated Android-based smartphones are already widely available on the market, with various contents that essentially increasingly pamper users. It is good that the use of smartphones as a means of telecommunications is not only for sharing news with relatives, friends or colleagues, but can also be used as a means to increase passive income. There needs to be an effort to find other breakthroughs to obtain income, one way is to find passive income via smartphone by using the earn money maker application. Training on passive income with the earn money maker application has never been carried out in Mangunsari Village, Gunungpati District, Semarang City, and it is even possible that it is rarely done in other places. This is because there are no competent people about the earn money maker application who can provide introduction and training to residents. The purpose of this training is to open the minds of residents so that they can make passive income by using various applications that can generate money from Android smartphones owned by residents. In the future, it is hoped that with this earn money maker for android training, it will increase residents' understanding and knowledge about various applications on Android smartphones that residents can use as an alternative to increase passive income. Keywords: earn money maker for android and passive income